PENGARUH MODEL PBL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Nanda, Fitra; Zainil, Melva; Zuryanti, - (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research aims to determine the effect of Problem Based Learning model (PBL) on students' mathematical problem solving skills in primary school in Bukittinggi.. The type of this research was experimental research with True Exsperimental design. The sample in this research were 2  classes, they are class IVA and class IVB SDN 02 Percontohan Bukittinggi. The calculation results of research data used was t-test obtained tcount 2.852> ttabel 1.671 at the level of α 0.05. Thus can be concluded that there was significant problem based learning model (PBL) to the students' mathematical problem solving skills of primary school in Bukittinggi.